2011
DOI: 10.1111/j.1365-2044.2011.06957.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of proximal femoral fractures 2011

Abstract: Summary  1. There should be protocol‐driven, fast‐track admission of patients with hip fractures through the emergency department.  2. Patients with hip fractures require multidisciplinary care, led by orthogeriatricians.  3. Surgery is the best analgesic for hip fractures.  4. Surgical repair of hip fractures should occur within 48 hours of hospital admission.  5. Surgery and anaesthesia must be undertaken by appropriately experienced surgeons and anaesthetists.  6. There must be high‐quality communication be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(62 citation statements)
references
References 33 publications
1
46
1
5
Order By: Relevance
“…Nationally, 30-day mortality is quoted at 8.1% in 2012-2013, with 86% of patients receiving surgery within 48 h [1][2][3]. In our study, we found that patients with a FNOF from the community closely matched these figures with regard to 30-day mortality (10.4%) and operative management within 48 h of presentation (88.4%).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Nationally, 30-day mortality is quoted at 8.1% in 2012-2013, with 86% of patients receiving surgery within 48 h [1][2][3]. In our study, we found that patients with a FNOF from the community closely matched these figures with regard to 30-day mortality (10.4%) and operative management within 48 h of presentation (88.4%).…”
Section: Discussionsupporting
confidence: 84%
“…Patients suffering this injury commonly pose a challenge medically as 17% of patients are noted to have two major co-morbidities and 7% have three or more [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…РЕКОМЕНДАЦИЯ 16: Всем пациентам с низко-травматическим переломом бедра рекомендуется хирур-гическое лечение у травматолога-ортопеда в течение 48 часов с последующей активизацией пациента [115][116][117].…”
Section: Rozh@endocrincentrruunclassified
“…Despite remarkable benefits of early surgery following hip fracture on outcomes and elderly patients exhibit numerous complications. The most common coexisting diseases include cardiovascular disease (35%), respiratory disease (14%) and cerebrovascular disease (13%), and ~70% of patients are classified as American Society of Anesthesiologists (ASA) stage III or IV (10) in poor health and time to surgery is prolonged due to direct oral anticoagulants and other factors, including waiting for routine medical clearance and unavailability of the operating suite or surgeon (11,12). In China, very elderly are frequently defined as ≥80 years old patients, and it has been estimated that the lifetime risk for an 80-year-old man or woman to sustain a hip fracture is 9 and 19%, respectively (13).…”
Section: Introductionmentioning
confidence: 99%